2020
DOI: 10.1111/ijcp.13704
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin index is a strong prognostic marker in adult hemophagocytic lymphohistiocytosis

Abstract: Aims The relationship between ferritin levels and survival in adult hemophagocytic lymphohistiocytosis (HLH) has been evaluated in previous studies. However, Admission‐to‐discharge percentage ferritin reduction (named as ferritin index) level in adult patients with HLH has never been evaluated to predict 6‐month survival. Methods The demographic, laboratory and clinical information of 102 newly diagnosed adult HLH patients were collected. Regression analysis, receiver operating curve and Kaplan‐Meier curves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The predominant cause of HLH differs in each country, with infections being the main trigger of adult HLH in USA, France, Spain and South Korea, while malignancies were most common in Italy, China and Japan, suggesting the probably speci c geographical distribution of triggering agents [14]. In consistence with previous studies [15][16][17], we found that malignancies especially lymphoma and leukemia were the most frequent cause of adult secondary HLH. While in another research, infections were reported as the most common cause of HLH [18].…”
Section: Discussionsupporting
confidence: 86%
“…The predominant cause of HLH differs in each country, with infections being the main trigger of adult HLH in USA, France, Spain and South Korea, while malignancies were most common in Italy, China and Japan, suggesting the probably speci c geographical distribution of triggering agents [14]. In consistence with previous studies [15][16][17], we found that malignancies especially lymphoma and leukemia were the most frequent cause of adult secondary HLH. While in another research, infections were reported as the most common cause of HLH [18].…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to previous studies, this paper focuses on the predictive value of ferritin for induction response in patients with HLH. Previous investigators have discussed the relationship between ferritin and the prognosis of patients at six months, one year and two years after treatment and conclude that serum ferritin is a good predictor of survival [ 21 , 22 ]. Our study also analysed the predictive role of ferritin on survival, and the results showed significant differences in survival among patients with different ferritin stratification at three to four weeks after induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…( Ghoneum et al, 2019 Apr );( Dignass et al, 2018 Mar ) ;( Lee et al, 2019 ) ;( Knaak et al, 2020 Jun 1 ) ;( Zhou et al, 2021 Mar ) ;( Worth et al, 2020 May ) ;( Martin-Bastida et al, 2017 May 3 ) ;( WHO international coronavirus disease (COVID-19) situation reports. Available online: https://www.who.int/emergencies/diseases/novel-coronavirus-, 2021 ) ;( Dave et al, 2021 Sep ) ;( Waizel-Haiat et al, 2021 Feb ) ;( Banerjee et al, 2021 Jun 7 ) ;( Cavezzi et al, 2020 May ) ;( Pongtanakul et al, 2017 Jun 19 ) ;( Birlutiu et al, 2021 ) .…”
Section: Uncited Referencesmentioning
confidence: 99%